Proposal of a Simplified Process to Correct the Phase Decoupling using Modal Analysis - Costa, E. C. M.; Kurokawa, S. [UNESP]; Pissolato, J.; IEEE (Ieee, 2012)
Modal analysis is widely approached in the classic theory of transmission line modeling. This technique is applied to model the three-phase representation of conventional electric systems taking into account their self and mutual electrical parameters. However the methodology has some particularities and inaccuracies for specific applications which are not clearly described in the basic references of this topic. This paper provides a thorough review of modal analysis theory applied to line models followed by an original and simple procedure to overcome the possible errors embedded in the modal decoupling through the three-phase system modeling.
Keywords: Transmission line modeling; modal analysis; modal transformation matrix; frequency/time domain